2013
DOI: 10.1371/journal.pgen.1003444
|View full text |Cite
|
Sign up to set email alerts
|

Functional IL6R 358Ala Allele Impairs Classical IL-6 Receptor Signaling and Influences Risk of Diverse Inflammatory Diseases

Abstract: Inflammation, which is directly regulated by interleukin-6 (IL-6) signaling, is implicated in the etiology of several chronic diseases. Although a common, non-synonymous variant in the IL-6 receptor gene (IL6R Asp358Ala; rs2228145 A>C) is associated with the risk of several common diseases, with the 358Ala allele conferring protection from coronary heart disease (CHD), rheumatoid arthritis (RA), atrial fibrillation (AF), abdominal aortic aneurysm (AAA), and increased susceptibility to asthma, the variant's eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
270
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(291 citation statements)
references
References 56 publications
16
270
5
Order By: Relevance
“…Whereas in humans a substantial fraction of serum sIL-6R can be attributed to alternative splicing of the IL-6R mRNA, the bulk of circulating sIL-6R appears to be generated by mechanisms distinct from differential mRNA splicing (13). A SNP within the ADAM17 cleavage site leads to increased serum sIL-6R levels in SNP carriers suggesting a decisive role of ectodomain shedding in serum sIL-6R generation (14,15). Surprisingly, hypomorphic ADAM17 ex/ex mice, which almost completely lack ADAM17 protein, exhibit unaltered serum sIL-6R levels pointing to the involvement of a different protease in serum sIL-6R generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in humans a substantial fraction of serum sIL-6R can be attributed to alternative splicing of the IL-6R mRNA, the bulk of circulating sIL-6R appears to be generated by mechanisms distinct from differential mRNA splicing (13). A SNP within the ADAM17 cleavage site leads to increased serum sIL-6R levels in SNP carriers suggesting a decisive role of ectodomain shedding in serum sIL-6R generation (14,15). Surprisingly, hypomorphic ADAM17 ex/ex mice, which almost completely lack ADAM17 protein, exhibit unaltered serum sIL-6R levels pointing to the involvement of a different protease in serum sIL-6R generation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum sIL-6R Is Not Released by ADAM10, ADAM8, Neutrophil Elastase, Cathepsin G, or Proteinase 3-A soluble form of the IL-6R is present in the blood of humans as well as mice and genome-wide association studies have reported a correlation between serum sIL-6R levels and the outcome of autoimmune diseases like asthma, rheumatoid arthritis, and type I diabetes (15,32). In that respect, it has been proposed that sIL-6R in conjunction with soluble gp130 (sgp130) in the blood operates as a buffer against IL-6 preventing global inflammation by overshooting IL-6 (33).…”
Section: Adam17 Is the Major Sheddase Of Pma-and Lps-induced Il-6r Shmentioning
confidence: 99%
“…The IL6R 48892C (358Ala) allele has been reported to affect proteolytic cleavage of the membrane-bound IL6R, leading to reduced numbers of the functioning IL6R (32). As a result, this genetic variant is suggested to contribute to anti-inflammatory effect through attenuation of IL6 signaling on cells expressing the membrane-bound IL6R (33)(34)(35). On the basis of our finding, the effect of reduced IL6R expression might be more prominent when the availability of IL6 is limited, whereas it might be overcome by overexpression of IL6.…”
Section: Discussionmentioning
confidence: 99%
“…The constitutive activation of STAT3 in cancer results from chronic stimulation by extracellular signals in the microenvironment, including IL6 (23), and overexpression of CD126 enhanced IL6/STAT3 responses (16,28). In CLL cells, in vivo constitutively activated STAT3 involves phosphorylation of serine 727 residues (p-STAT3 S727 ) but not tyrosine 705 residues (19).…”
Section: Cd126 Expression On Cll Cells Correlates With Stat3 Activitymentioning
confidence: 99%